Laboratory Tests of New Connectors for Timber-Concrete Composite Structures - SZUMIGAŁA, Maciej; SZUMIGAŁA, Ewa; POLUS, Łukasz (Engineering Transactions, 2018)
This paper presents the results of the laboratory tests of new connectors for timber-concrete composite (TCC) structures. These connectors can be used to join a timber beam with a concrete slab. They consist of two parts – a headed stud and a steel screw. The objective of our analysis was to examine the stiffness and strength of the connection, which can be used in designing TCC beams. The authors introduced formulas for calculating the above mentioned parameters. The results obtained in the experimental tests are compared with those calculated using the proposed formulas.